2020
DOI: 10.1371/journal.pone.0229278
|View full text |Cite
|
Sign up to set email alerts
|

Super resolution measurement of collagen fibers in biological samples: Validation of a commercial solution for multiphoton microscopy

Abstract: Multiphoton microscopy is a powerful, non-invasive technique to image biological specimens. One current limitation of multiphoton microscopy is resolution as many of the biological molecules and structures investigated by research groups are similar in size or smaller than the diffraction limit. To date, the combination of multiphoton and super-resolution imaging has proved technically challenging for biology focused laboratories to implement. Here we validate that the commercial super-resolution Airyscan dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Imaging and cellular analysis of airway fibroblasts. Collagen I gels were fixed in 4% paraformaldehyde, stained with 4' ,6-diamidino-2-phenylindole (DAPI) to identify nuclei, Phalloidin (Thermo-Fisher Scientific, Waltham, USA) for F-actin, and E-cadherin using a rabbit monoclonal (DECMA-1) antibody (Abcam, ab11512), then imaged at 20x magnification using a Zeiss LSM-880 inverted confocal microscope (Carl-Zeiss, Germany), with a Coherent Chameleon Ultra II femtosecond Ti:sapphire laser (Coherent, CA) 54 . The cell area and cell numbers of PAFs within collagen gels were determined with Fiji as previously described 23 .…”
Section: See Online Supplement For Full Methods Sample Collection Pmentioning
confidence: 99%
“…Imaging and cellular analysis of airway fibroblasts. Collagen I gels were fixed in 4% paraformaldehyde, stained with 4' ,6-diamidino-2-phenylindole (DAPI) to identify nuclei, Phalloidin (Thermo-Fisher Scientific, Waltham, USA) for F-actin, and E-cadherin using a rabbit monoclonal (DECMA-1) antibody (Abcam, ab11512), then imaged at 20x magnification using a Zeiss LSM-880 inverted confocal microscope (Carl-Zeiss, Germany), with a Coherent Chameleon Ultra II femtosecond Ti:sapphire laser (Coherent, CA) 54 . The cell area and cell numbers of PAFs within collagen gels were determined with Fiji as previously described 23 .…”
Section: See Online Supplement For Full Methods Sample Collection Pmentioning
confidence: 99%
“…In summary, we have described a thorough theoretical description of SHG‐PR. Existing, standard SHG microscope can readily be transformed into SHG‐PR systems by replacing the point detector with a position‐sensitive camera or Airyscan detector for SHG signal detection (Barlow et al ., 2020). Then, a whole image for the excited region will be recorded for each position of the scanning focus.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Barlow et al has shown use of the Zeiss Airyscan (a 32-channel GaAsP photomultiplier tube (PMT) array detector (17)) on top of MPM and SHG imaging can improve resolution up by a factor of 1.7× (18).…”
Section: Introductionmentioning
confidence: 99%